2020
DOI: 10.3390/su12031072
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability: Nutrition and Dietetic Students’ Perceptions

Abstract: Opportunities exist for nutrition and dietetic (N&D) professionals to contribute to sustainable development and support actions towards the attainment of the UN’s Sustainable Development Goals (SGD’s). Students undertaking higher education are well-placed to develop skills and capabilities in creative and critical problem solving for sustainability. However, there is limited literature exploring nutrition and dietetic students’ perceptions of sustainability that would help to inform an effective and constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0
4

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 13 publications
4
35
0
4
Order By: Relevance
“…While there is increasing motivation and intention among young adults to act more sustainably, it must be recognized that university student's experiences are diverse, and the key demographic and educational characteristics of Australian university students who perceive sustainable food choices as important remains unknown. One Australian study has identified that most of the undergraduate students studying nutrition and dietetics surveyed reported that sustainable foods were important to them [19]. However, university students are clearly not a homogeneous group, and the perceptions of the importance of sustainable foods in Australian university students across a wider number of disciplines would build on this knowledge.…”
Section: University Students Perceptions Of Sustainable Foodsmentioning
confidence: 99%
“…While there is increasing motivation and intention among young adults to act more sustainably, it must be recognized that university student's experiences are diverse, and the key demographic and educational characteristics of Australian university students who perceive sustainable food choices as important remains unknown. One Australian study has identified that most of the undergraduate students studying nutrition and dietetics surveyed reported that sustainable foods were important to them [19]. However, university students are clearly not a homogeneous group, and the perceptions of the importance of sustainable foods in Australian university students across a wider number of disciplines would build on this knowledge.…”
Section: University Students Perceptions Of Sustainable Foodsmentioning
confidence: 99%
“…In addition to needing greater incorporation of environmental sustainability into curricula for undergraduate and postgraduate nutrition/dietetics courses, increases in nutrition and dietetics students' knowledge, skills, and self-efficacy to implement such practices are also required [46,47]. In 2020, Burkhart et al [46] found that students had varying levels of familiarity with sustainability-related concepts around economic resilience, environmental integrity, social development, and cross-cutting issues. Most (82%) students thought sustainability was very important in general, with almost two-thirds (63%) recognizing sustainability was specifically important for professional practice [46].…”
Section: Resultsmentioning
confidence: 99%
“…In 2020, Burkhart et al [46] found that students had varying levels of familiarity with sustainability-related concepts around economic resilience, environmental integrity, social development, and cross-cutting issues. Most (82%) students thought sustainability was very important in general, with almost two-thirds (63%) recognizing sustainability was specifically important for professional practice [46]. Early and mid-career nutrition/dietetics professionals who are working in and managing food procurement and foodservice roles require upskilling and bolstered confidence to implement state-of-science practices to ensure Australia's health services and aged care facilities adopt recommended actions.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors have recognized that, when sustainability is mentioned, people generally refer exclusively to the environmental dimension [11][12][13][14], especially due to the influence of the media on issues related to the environment [11], while the social and economic dimensions are relegated in many cases [11,12,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to promote sustainable development and sustainability, decision-makers, policymakers, and the scientific and educational communities should act with a broader vision, encompassing all dimensions of sustainability, and develop creative, ethical, trained, and competent thinkers [11] who will improve living conditions for all citizens.…”
Section: Introductionmentioning
confidence: 99%